Nghiên cứu ảnh hưởng của tương tác khách hàng và nhận dạng thương hiệu đến sự hài lòng của khách hàng - Trần Thị, Lâm; Phan Chí , Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study explores the impact of customer engagement on customer satisfaction with the coffee products that they are experienced at coffee shops through the mediating variable of customer identification. The survey was conducted with 253 customers in the period from January to March 2023. The results are analyzed quantitatively and used to test the model and research hypotheses through SPSS 26 and AMOS 20 software. Research results show that only the cognitive engagement factor in the general customer engagement variable has a positive and direct impact on customer satisfaction. Besides, all components of customer engagement variables (cognition, emotions, and behavior) have an impact on satisfaction with coffee products through the intermediate variable of customer identification. As a consequence, the study suggests some solutions and implications for businesses and coffee shop chains to improve customer satisfaction and customer identification and theoretical implications for future research on the same topic.